1999
DOI: 10.2323/jgam.45.283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation of keratin by two species of Bacillus.

Abstract: Keratinolytic microbes represent an important component of soil biocenosis where they mineralize a highly resistant proteinaceous substrate "keratin" of vertebrate skin and its adnexes. Most research on the biodegradation of keratin has been carried out with dermatophytic (Deshmukh and Agrawal, 1985;Evans and Hose, 1975;Kunert, 1989) and nondermatophytic (Rajak et al., 1991(Rajak et al., , 1992 fungi and actinomycetes (Kunert, 1989;Noval and Nickerson, 1959), and the work with bacterial species has been little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…However, the induction of keratinolytic enzyme produced by the species of Bacillus with feather powder, human hair and nails, and cow horn and hooves was reported (Cheng et al 1995;Lal et al 1999). The keratinase production from B. licheniformis FK 14 reached a maximum in the late logarithmic growth phase similar to those reported by Lin et al (1992), Sangali & Brandelli (2000b) and Kim et al (2001).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, the induction of keratinolytic enzyme produced by the species of Bacillus with feather powder, human hair and nails, and cow horn and hooves was reported (Cheng et al 1995;Lal et al 1999). The keratinase production from B. licheniformis FK 14 reached a maximum in the late logarithmic growth phase similar to those reported by Lin et al (1992), Sangali & Brandelli (2000b) and Kim et al (2001).…”
Section: Discussionsupporting
confidence: 73%
“…Bacillus species have been reported to produce keratinolytic protease (Lin et al 1992;Altalo & Gashe 1993;Cheng et al 1995;Lal et al 1999;Lin et al 1999;Kim et al 2001;Lee et al 2002). However, this strain isolated from Thai soil grew and degraded feather well at elevated temperatures.…”
Section: Discussionmentioning
confidence: 93%
“…Accompanied by feather degradation and keratinase production, the pH value of the culture increased to about 8.5. B. subtilis strains had been widely utilized for enzyme production, including the keratinases (Lal et al, 1999;Suh and Lee, 2001;Kim et al, 2001;Macedo et al, 2005). Other Bacillus species including B. licheniformis, B. pumilis, B. cereus, B. halodurans and B. pseudofirmus (Williams et al, 1990;Takami et al, 1999;Rozs et al, 2001;Kim et al, 2001;Gessesse et al, 2003;El-Refai et al, 2005) had also been reported for their keratinolytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, maximum keratinase production was recorded after eight days of culture. Likewise, one of the strains inquired by Lal et al (19), B. licheniformis S23, exhibited great capability of human hair decomposition, especially in prolonged cultures. Maximum keratinase activity was obtained after one month of cultivation and the amount of reduced thiols reached nearly 0.3 mM, proving strains keratinolytic action against hair, in contrast to cow hoove or horn and human nail material.…”
Section: Discussionmentioning
confidence: 96%